ANALISIS MULTIVARIAT : PENGKAJIAN PENGETAHUAN, SIKAP DAN DETERMINASI NIAT PENERIMAAN VAKSIN COVID-19 PADA WARGA KELURAHAN PEJUANG KOTA BEKASI - Adin Hakim Kurniawan; Yetri Elisya; Muhammad Fregi Marsa (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2021)
One of the efforts of the Indonesian government to fight Covid 19 is to hold vaccinations for all Indonesian people. DKI Jakarta is one of the epicenters of the spread of Covid 19 which was the beginning of starting vaccination activities. There is still many people's rejection of the implementation of complete basic immunization including Covid 19 vaccination. Objective: To determine knowledge, attitudes, acceptance, and factors that influence the acceptance of Covid 19 vaccine. This research type of quantitative descriptive with cross-sectional design. The sampling technique used cluster stratified sampling. The number of research respondents was 136 people. Statistical analysis techniques are chi-square and multiple regression logistic multivariate. Results: This study revealed a good level of knowledge (52.94%), positive attitudes (59.82%), and intention to receive the COVID-19 vaccine (75.70%). From the logistic regression analysis, the factors that had a significant relationship with vaccine acceptance were: a history of degenerative diseases (p-value=0.004); knowledge about the covid 19 vaccine (p-value = 0.010), and an attitude of agreeing to accept Covid 19 (p = 0.026). Vaccine knowledge education and communication from government sources is an important method to reduce negative attitudes towards COVID-19 vaccines.